Features of Polish Companies. Results of the Company Competitiveness Barometer 2014 - Olaf Flak; Grzegorz Glod (Institute of Economic Research (IER), 2015)
In the paper there are results of the research on competitiveness of Polish companies which was conducted within the Company Competitiveness Barometer in 2014. The paper includes a short description of the integrated company competitiveness model, their integral elements and methodology of the research. Then there are results of a competitive potential, a strategy of competition, a competitive advantage, a competitive position of examined companies. 252 companies took part in the Company Competitiveness Barometer 2014. Answers to the survey placed on www.konkurencyjniprzetrwaja.pl let get knowledge about some sample of Polish companies in different sectors of economy. The data was also a foundation to verify some theoretical assumptions of relations between the elements of competitiveness.
Keywords: 330; company competitiveness; competitive advantage; competitive potential; strategy of competition; competitive positioning